PARTISIPATORY ACTION RESEARCH (PAR) IMPLEMENTASI KEBIJAKAN WAJIB BELAJAR PENDIDIKAN DASAR SEMBILAN TAHUN DI KABUPATEN SERANG - Engkos Kosasih (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2018)
Education is the most important aspect in nation building. Quality human resources will only be realized from quality education. Education distribution strategy should get main priority because in reality there are still children in Serang District who dropped out of school or did not continue their education, especially in elementary education level. The government's step in dealing with the problem of dropping out of school in Serang Regency with the promulgation of the compulsory 9-year basic education should be continued. Because in the implementation there are still some inhibiting factors, such as, the state of the economy, the circumstances of social and cultural environment, facilities of education and community participation. This study aims to determine the constraints faced, how the socialization, and what kind of characteristics of school drop outs. This research uses qualitative approach and descriptive by using Partisipatory Action Reseach (PAR) method. The presence of researchers in this study as the main instrument in collecting data until the reporting stage of the results. Source of data used in this research is primary data source, FGD, interview and narrative. The Researcher becomes the key informant and supporting informant chosen purposively. The results of the research formulation of the problem shows that there are obstacles faced by the Government of Serang Regency in the success of wajardikdas program, such as: Demographic-Economy, Culture, Human Resources, Budget Limitations, Monitoring and Evaluation, Validity Data obtained and lack of socialization, Understanding of the characteristics of school drop outs.